Static Culture of Spirulina in Filtered Sago Effluent (FSE) - Nurhamizah, Merali (Universiti Malaysia Sarawak, UNIMAS, 2010)
Different concentrations of NaHCO3, a carbon source in the form of bicarbonate, were supplied to study the effects of carbon input on growth of Spirulina platensis. A static culture, setup of 2 L bottle equipped with aeration pump with 10% (v/v) concentration of Spirulina was cultured in filtered sago effluent (FSE) amended with different concentration of NaHCO3, 4 g/L, 8 g/L and 0 g/L (blank) was exposed under outdoor sunlight while Zarrouk’s medium was used as positive control. The study was conducted for 20 days and was done twice. The result shows that FSE with 4 g/L NaHCO3 have a higher biomass and followed by 8 g/L NaHCO3 and blank. Protein content in gram percentage yield also shows that FSE with 4 g/L NaHCO3 is the highest among FSE medium. Hence, the cultivation of Spirulina platensis in static culture of FSE amended with NaHCO3 shows 4 g/L is the best.